2015
DOI: 10.1080/00958972.2015.1031120
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, computational, antimicrobial andin vitroanticancer studies of copper(II) complexes with N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine and tris(2-hydroxyethyl)amine

Abstract: The present work consists of synthesis, structural characterization, spectral, DFT, antimicrobial and anticancer studies of two copper(II) complexes, [Cu(THEEN)(DNB)](DNB) (1) and [Cu(TEAH 3 ) 2 ](DNB) 2 (2). In these complexes, THEEN is N,N,N′,N′-tetrakis(2-hydroxyethyl)ethylenediamine, a tetrapodal ligand, and TEAH 3 is tris(2-hydroxyethyl)amine, a tripodal ligand, and the counter anion is 3,5-dinitrobenzoate (DNB -). X-ray crystallography studies reveal that both complexes have distorted octahedron geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…As reported by Karlin and Zubieta (Eds. ), if the G > 4, the exchange interaction was insignificant due to local tetragonal axes that were aligned parallel. If the G < 4, the exchange interaction was reasonable and the local tetragonal axes were misaligned.…”
Section: Resultsmentioning
confidence: 99%
“…As reported by Karlin and Zubieta (Eds. ), if the G > 4, the exchange interaction was insignificant due to local tetragonal axes that were aligned parallel. If the G < 4, the exchange interaction was reasonable and the local tetragonal axes were misaligned.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the researchers examined the antitumor properties of the Cu complex. They observed that the Cu complexes show good antitumor properties [31,32].…”
Section: Antioxidant and Antitumor Activity Of The Complexesmentioning
confidence: 99%
“…Several tripodal amines have been investigated as anticancer agents, alone or bounded to metal centers [18,19,20,21,22,23,24,25,26,27,28,29]. The family of tetradentate tripodal amines have a general structure consisting of a central donor atom of nitrogen attached to three independent arms, each one also containing at least one methylene group and a donor atom.…”
Section: Introductionmentioning
confidence: 99%